(3HZjI GdhYGI aj WHbGJ GddZhjjf hGdfMGIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3CMeO Hf NWGH Hf YeQ GdefTGhi s)
(3ChdgG (B:s
(3GdMeO ddg NGdb GdhLhO heYOeI , heGfM GdaVd hedgeg CeG HYO , aEfi efP fTCJ hCfG CJThb Edi cJGH jLeY CNHGQ GdfMhjjf ahbYJ Ydi WHbGJ GdfMGI GdHUQjjf dCHi SYjO GdSjQGai s
(3BNQgG (B:s
(3heYLe GdCOHGA djGbhJ GdMehi , hGdfVGQ dCHi MjGf , Edi ZjQ Pdc ef GdeYGLe hGdJYGdjb GdJi dGJMUi , hGddg CSCd GdJhajb deG jQUjg , hGdgOGjI ajeG GPQg hBJjg , hCf dGjLYd YdefG MLI YdjfG BNQ WHbGJ GdfMGI GdUZQi s
(3QJHg GdeDda Ydi MQha GdeYLe hGHJOCg HGdeMeOjf aGdCMeOjf JHQckG, hai BNQg HGH ai Gdcfi hGdCdbGH hGdfSH hGdEVGaGJs
(3HChdgG Jedc dHOQ GdOjf GdbQGai YGe (B979(3g` hJedc BNQ SfI (B1024(3g` hKGdK SfI (B11 s
(3aQZ ef JCdjaI ai TgQ QeVGf SfI (B871(3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdJGQjNs